Understanding pendulums a brief introduction - Pook, L.P.; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
"Despite their apparent simplicity, the behaviour of pendulums can be remarkably complicated. Historically, pendulums for specific purposes have been developed using a combination of simplified theory and trial and error. There do not appear to be any introductory books on pendulums, written at an intermediate level, and covering a wide range of topics. This book aims to fill the gap. It is written for readers with some background in elementary geometry, algebra, trigonometry and calculus." p. 4 of cover
Electronic reproduction.
Keywords: Pendulum; Electronic books